The causal effects of dietary component intake and blood metabolites on risk of delirium: a Mendelian randomization study - Zhu, Qian; Liu, Yingjian; Li, Xiaona; Wang, Chao; Xie, Zhenyan; Guo, Gongjie; Gu, Wenqing; Hu, Yongzhen; Wei, Xiaobing; Wen, Yiqi; Jing, Yingchao; Zhong, Shilong; et al. (Frontiers in Nutrition, 2024)
Growing evidence has indicated that the nutritional quality of dietary intake and alterations in blood metabolites were related to human brain activity. This study aims to investigate the causal relationship between dietary component intake, blood metabolites, and delirium risks.We performed Mendelian randomization (MR) analysis using genetic variants as instrumental variables for dietary component intake, blood metabolites, and delirium.Inverse variance weighting, maximum likelihood, weighted median, weighted mode, and MR-Egger methods were used for statistical analyses.We found that genetic prediction of salt added to food (odds ratio [OR] 1.715, 95% confidence interval [CI] 1.239-2.374, P = 0.001) significantly increased the risks of delirium, while low-fat polyunsaturated margarine used in cooking (OR 0.044, 95%CI 0.004-0.432, P = 0.007), cheese intake (OR 0.691, 95%CI 0.500-0.955, P = 0.025) and coffee intake (OR 0.595, 95%CI 0.370-0.956, P = 0.032) was suggestively associated with decreased risks of delirium. Moreover, increased blood 1-stearoylglycerol levels (OR 0.187, 95%CI 0.080-0.435, P = 9.97E-05) significantly contributed to reducing the risks of delirium. 3-methoxytyrosine (OR 0.359, 95%CI 0.154-0.841, P = 0.018) also has the potential to decrease the risk of delirium.Our study highlights the potential causal effect relationships of dietary component intake and blood metabolites on the risk of delirium, which potentially provides novel insights into targeted dietary prevention strategies or biomarkers for delirium.